Construction and validation of customer value co-creation attitude scale - Shamim, A. (Emerald Group Publishing Ltd., 2017)
Purpose: The purpose of this research is to develop a scale for measuring customer value co-creation attitude (CVCCA). Design/methodology/approach: Scale development procedures are used for item generation, item purification and validation. Two studies are conducted. In Study 1, exploratory and confirmatory factor analysis is used to generate and confirm the factorial structure of the CVCCA construct. Study 2 validates the scale on a large field sample. Findings: The study develops a new scale for measuring CVCCA. Results suggest that CVCCA is a higher-order construct comprising three dimensions: interaction attitude, knowledge sharing attitude and responsive attitude. Additionally, experiential value significantly predicts CVCCA, which subsequently leads to customer value co-creation behaviour confirming nomological validity of the scale. Research limitations/implications: The CVCCA scale should be of interest for researchers in exploring factors and outcomes of CVCCA. The scale is useful to managers who are interested in measuring their customers’ co-creation of value attitude and their willingness to engage in value co-creation behaviour. Originality/value: This is the first scale using the service logic of marketing lens. The scale is found to be a valid and reliable tool to measure customer attitude to engage in value co-creation. © 2017, © Emerald Publishing Limited.